9.3.1 Can Systems Engineering Support An Owner Operator Organisation When Faced With The Challenge Of Being A Design Authority?. Issue 1 (July 2014) - Cowper, Doug; Gallagher, Ian; Krolikowski, Andrew; McGrogan, Nick
Abstract Over the years acquisition methodologies, e.g. BVP, have resulted in a shift in engineering procurement where large organisations have been increasingly asking their supply chain to take on the responsibility for part of, or overall system design. However, just handing over a set of requirements to a supplier and then waiting for them to deliver is a high risk strategy especially with novel/complex programmes. To reduce the risk of problems and to comply with some regulatory environments, the intelligent customer needs to take design responsibility by focusing on technically assuring that the system will be 'fit for purpose'. This paper explores the issues facing an owner operator who needs to be the Design Authority, identifies aspects of SE that require further work to support an Owner DA, and shows how SE can support a DA on a complex systems programme in such a shared design management arrangement and regulated environment.